Autorzy:M.Dobrowolska
Wydawnictwo:GWO
Rok wydania:2015
Czy po przekształceniu podanego wyrażenia 4.52 gwiazdek na podstawie 21 opinii

Czy po przekształceniu podanego wyrażenia

1Zadanie
2Zadanie
3Zadanie
4Zadanie
5Zadanie

`a)\ 3x-(2x+4y)+(5x+y)=ul(3x)-ul(2x)-ul(ul(4y))+ul(5x)+ul(ul(y))=6x-3y\ \ \ \ \ TAK` 

`b)\ (4a-2b)-(6b-2a)-6a=ul(4a)-ul(ul(2b))-ul(ul(6b))+ul(2a)-ul(6a)=-8b\ \ \ \ \ TAK` 

`c)\ -(3m+2n)-(2m-5n)+4n=ul(-3m)-ul(ul(2n))-ul(2m)+ul(ul(5n))+ul(ul(4n))=-5m+7n\ \ \ \ \ NIE` 

`d)\ strike10^5xy^2*1/strike2^1xy-2x=5x^2y^3-2x\ \ \ \ \ \ NIE`